Absolute Lymphocyte Count; the most Sensitive Indicator of the Risk of Progression and Complications in COVID-19 - Ali, Kamran; Nawaz, Khurram Haq; Ul Hassan, Wahaj; Waqar, Raja Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To explore the role of lymphocyte count as a predictor of severity biomarkers in COVID-19 patients.Study Design: Comparative cross-sectional study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2020 to Jan 2021.Methodology: A total of 120 patients were enrolled for this study. We analyzed the blood samples of the affected patient in a certified laboratory. From blood samples, we deduced information related to leucocyte count, neutrophils, lymphocyte (cells×109/L) counts, ferritin (ng/mL), CRP (mg/dL), d-Dimer (mg/mL), lactate dehydrogenase (LDH, U/L) and lymphocyte subsets.Results: In critical condition cases, we observed a massive decrease in CD3+CD4+T cell count by 49% (278+124.53 vs 545+138.32), CD4+/CD8+ratio by 30% (0.72+0.14vs1.00+0.04) and CD4+MFI by 17% (21834+1150.03 vs 26287+920.86) as compared to the Non-Critical Group (p-value